2022
DOI: 10.3390/risks10090168
|View full text |Cite
|
Sign up to set email alerts
|

Does the Adaptive Market Hypothesis Reconcile the Behavioral Finance and the Efficient Market Hypothesis?

Abstract: This study aims to test the adaptive market hypothesis by using the myopic behavior of investors as a new proxy. The data have been taken from New York Stock Exchange from December 1994 to December 2020. Following this collection of data, the companies’ stock prices were distributed into six different portfolios based on size, investment, a book-to-market value, and operating profit. Ordinal logistic regression was used to calculate the probability of recovery of losses after experiencing a decline in the mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Additionally, Soni, K., & Desai, M. conducted grouped surveys based on different age and gender categories and found that variations in risk tolerance among different age groups can impact investors' decision-making [4]. Consequently, the rise of behavioral finance, which incorporates emotional factors and investors' irrational behavior, has led to the development of behavioral portfolio theory (BPT) as a more comprehensive investment strategy [5][6][7]. It is suggested for application in real markets.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Soni, K., & Desai, M. conducted grouped surveys based on different age and gender categories and found that variations in risk tolerance among different age groups can impact investors' decision-making [4]. Consequently, the rise of behavioral finance, which incorporates emotional factors and investors' irrational behavior, has led to the development of behavioral portfolio theory (BPT) as a more comprehensive investment strategy [5][6][7]. It is suggested for application in real markets.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…Such unforeseen events can affect investors' purchasing power and the stock prices of various industries, deviating from predictions based on historical data and contradicting theoretical assumptions. Therefore, in Noreen et al's article, they proposed the Adaptive Market Hypothesis, suggesting that markets may not swiftly adjust to restore equilibrium in certain situations [7]. Investors may remain rational under normal circumstances but become irrational during exceptional periods.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…Te stock price can be afected by news, events, and information about the release of new products. Information determines the movement of fnancial markets according to the efcient market hypothesis (EMH) [12]. Te EMH model assumes that stock prices are determined by a random walk model.…”
Section: Literature Reviewmentioning
confidence: 99%